Comparison of the Incidence of Postdural Puncture Headache Following Spinal Anesthesia in Cesarean Sections Using 25g and 27g Needles With Median and Paramedian Approaches - Khan, Samreen; Naseem, Chanda; Khan, Muhammad Arsalan; Shahid Ullah; Abdur Rehman; Muhammad Tayyeb; Ahmad, Fawad; Najeeb, Maheen (Indus Journal of Bioscience Research, 2025)
Background: The occurrence and intensity of PDPH can be affected by several factors, including the caliber of the spinal needle and the technique employed during anesthesia. Although the median approach is conventionally used, the paramedian approach may provide advantages in some instances. This study aims to assess the incidence of postdural puncture headache (PDPH) after spinal anesthesia in cesarean sections with 25G and 27G needles via median and paramedian techniques. Materials and Methods: This six-month cohort study at Health Net, Peshawar, analyzed 200 C-section patients, grouped by spinal needle gauge (25G, 27G) and method (median, paramedian). Spinal anesthesia with 0.75% Bupivacaine was used, and PDPH incidence was monitored for five days. Results: The study found a 25% incidence of postdural puncture headache (PDPH), higher in the 25G needle group (35%) than the 27G group (15%; p = 0.01). The median spinal approach had a slightly higher PDPH rate (27.3%) than the paramedian method (22.2%; p = 0.25). Significant predictors included 25G needle use (OR = 28.2; p < 0.001), repeated puncture attempts (OR = 7.5; p < 0.001), and age ≥30 years (OR = 4.5; p < 0.001). Increased PDPH risk was also linked to blood loss ≥500 mL (OR = 5.2; p < 0.001) and the sitting position (OR = 1.8; p = 0.09). Conclusion: The research revealed a higher incidence of PDPH associated with 25G needles in comparison to 27G, with several attempts and patient variables also playing a role. Utilizing smaller-gauge needles and limiting attempts can significantly decrease the incidence of PDPH in patients undergoing cesarean sections.